2020
DOI: 10.1001/jamainternmed.2020.4055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Smartphone Applications for Smoking Cessation

Abstract: IMPORTANCE Smoking is a leading cause of premature death globally. Smartphone applications for smoking cessation are ubiquitous and address barriers to accessing traditional treatments, yet there is limited evidence for their efficacy.OBJECTIVE To determine the efficacy of a smartphone application for smoking cessation based on acceptance and commitment therapy (ACT) vs a National Cancer Institute smoking cessation application based on US clinical practice guidelines (USCPG). DESIGN, SETTING, AND PARTICIPANTSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
121
3
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 38 publications
15
121
3
7
Order By: Relevance
“…We did not find comparable data in studies that included interventions similar to Pivot. Broadening the scope to include additional digital smoking cessation interventions, 6-month 30-day PPA outcomes ranged from 12.9% to 21.8%, with an additional study reporting a 26.2% 30-day PPA rate at 8 weeks [10,34,40]. Similar to our expectation, we believe that the additional features of Pivot beyond the app likely contributed to the higher 30-day PPA rate.…”
Section: Ppa Ratessupporting
confidence: 74%
See 2 more Smart Citations
“…We did not find comparable data in studies that included interventions similar to Pivot. Broadening the scope to include additional digital smoking cessation interventions, 6-month 30-day PPA outcomes ranged from 12.9% to 21.8%, with an additional study reporting a 26.2% 30-day PPA rate at 8 weeks [10,34,40]. Similar to our expectation, we believe that the additional features of Pivot beyond the app likely contributed to the higher 30-day PPA rate.…”
Section: Ppa Ratessupporting
confidence: 74%
“…Looking more broadly at outcomes from digital smoking cessation interventions, 7-day PPA at 6 months range from 9.8% to 29.6%, with most falling between 17% and 25% [10,37,38,40,41]. Our higher 7-day PPA rate of 35.4% aligns with expectations considering Pivot's additional features of the personal breath sensor and coaching.…”
Section: Ppa Ratessupporting
confidence: 60%
See 1 more Smart Citation
“…With these measures in place, healthcare systems had to rapidly transition from in-person encounters to remote or virtual care methods [22,23]. To date, digital cessation aids including mobile applications and text message programs have effectively promoted self-efficacy and increased abstinence [24][25][26]. With smoking being one of the main preventable causes of COVID-19 progression, smokers may be more inclined to seek out treatment options at this time.…”
Section: Introductionmentioning
confidence: 99%
“…Further, promoting tech-driven approach by using quitting smoking apps is more beneficial to increase the odds of quitting success. A randomised clinical trial published recently compared the efficacy of two smartphone applications for smoking cessation, and found that smokers who used the iCanQuit app (teaches acceptance of smoking triggers) had 1.49 times higher odds of quitting smoking compared with those who used the QuitGuide app (depends on avoiding smoking triggers) 34 . This elevates apps as an effective way of quitting smoking, particularly apps that depend on accepting the existence of cravings rather than trying to eliminate them.…”
Section: How Can We Support Smoking Cessation During the Covid-19 Pandemic?mentioning
confidence: 99%